Think Pair Share Untuk Peningkatan Belajar Siswa Dalam Menyusun Kertas Kerja - -, Haronal (Jurnal Dewantara, 2016)
The improving learning achievement of students of class XI IPS 1 in preparing the working paper to use media power point presentation. The problems of this class action research is how to use the learning model Think Pair Share (TPS) with media power point affects the learning process, how big increase learning achievement, especially completeness of learners. Mastery learning in the first cycle increased by 21.88% and the second cycle increased by 53.13% when compared to prior studies class actions, which only reached 37, 5%.